2004
DOI: 10.1063/1.1808507
|View full text |Cite
|
Sign up to set email alerts
|

A controllable nanomechanical memory element

Abstract: Articles you may be interested inModeling and simulation for the enhancement of electron storage in a stacked multilayer nanocrystallite silicon floating gate memory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
120
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 14 publications
1
120
0
Order By: Relevance
“…The fabrication of micro/nano-electromechanical systems (MEMS/NEMS) is made possible due to the advancing technologies and state-of-art in the fields of micro/nanometrescale processing and machining [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. As its characteristic frequency scales upwards with decreasing size [9], micro/nanometre-scale mechanical resonator/oscillator with high and ultrahigh characteristic frequency is suitable for those applications requiring both high responsivity and high frequency operation [10], such as charge detection [2], ultra-sensitive mass sensing [7,[12][13][14][15][16][17], signal processing/mixing [8] and possible quantum effect study on a macroscopic system [11].…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of micro/nano-electromechanical systems (MEMS/NEMS) is made possible due to the advancing technologies and state-of-art in the fields of micro/nanometrescale processing and machining [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. As its characteristic frequency scales upwards with decreasing size [9], micro/nanometre-scale mechanical resonator/oscillator with high and ultrahigh characteristic frequency is suitable for those applications requiring both high responsivity and high frequency operation [10], such as charge detection [2], ultra-sensitive mass sensing [7,[12][13][14][15][16][17], signal processing/mixing [8] and possible quantum effect study on a macroscopic system [11].…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of the use of a nanoelectromechanical system (NEMS) as a memory element has been demonstrated in a number of experimental investigations [1][2][3][4][5][6][7][8] . It has been suggested that in order to increase the frequency of operation, oscillatory states (cycles) should be used as the stationary states of memory elements, with consequential switching between two cycles.…”
mentioning
confidence: 99%
“…The switching between the states is induced by an external control signal. Various strategies to control the switching have been discussed and experimentally validated 1,[4][5][6][7][8] . A complex dependence of switching on parameters of the control signal was observed by Unterreithmeier et al 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations